Stratigraphic architecture and fault offsets of alluvial terraces at Te Marua, Wellington fault, New Zealand, revealed by pseudo‐3D GPR investigation. Issue 8 (22nd August 2013) - Beauprêtre, S.; Manighetti, I.; Garambois, S.; Malavieille, J.; Dominguez, S.
Abstract: [1] Past earthquake slips on faults are commonly determined by measuring morphological offsets at current ground surface. Because those offsets might not always be well preserved, we examine whether the first 10 m below ground surface contains relevant information to complement them. We focus on the Te Marua site, New Zealand, where 11 alluvial terraces have been dextrally offset by the Wellington fault. We investigated the site using pseudo‐3D Ground Penetrating Radar and also produced a high‐resolution digital elevation model (DEM) of the zone to constrain the surface slip record. The GPR data reveal additional information: (1) they image the 3D stratigraphic architecture of the seven youngest terraces and show that they are strath terraces carved into graywacke bedrock. Each strath surface is overlain by 3–5 m of horizontally bedded gravel sheets, including two pronounced and traceable reflectors; (2) thanks to the multilayer architecture, terrace risers and channels are imaged at three depths and their lateral offsets can be measured three to four times, constraining respective offsets and their uncertainties more reliably; and (3) the offsets are better preserved in the subsurface than at the ground surface, likely due to subsequent erosion‐deposition on the latter. From surface and subsurface data, we infer that Te Marua has recorded six cumulative offsets of 2.9, 7.6, 18, 23.2, 26, and 31 m (± 1–2 m). Large earthquakes on southern Wellington fault might produce 3–5 m of slip, slightly less than previously proposed. Pseudo‐3D GPR thus provides a novel paleoseismological tool to complement and refine surface investigations. Key Points: Pseudo‐3D GPR is a novel powerful paleoseismological tool Pseudo‐3D GPR provides new information on past earthquake slip Pseudo‐3D GPR reveals 3D architecture of alluvial terraces